Natural History and Management of Hepatitis C: Does Sex Play a Role?. (15th July 2014) - Baden, Rachel; Rockstroh, Jürgen K.; Buti, Maria
Abstract : Hepatitis C virus infection is a disease that disproportionately affects men more than women. After initial HCV infection, women are more likely to clear the virus spontaneously. Women also have slower rates of liver disease progression than men if they become chronically infected. However, this rate of disease progression changes over time in women. Postmenopausal women have increased rates of fibrosis compared with women of reproductive age because they have lost the protective effects of estrogen. Estradiol and estrogen receptors in the liver protect hepatocytes from oxidative stress, inflammatory injury, and cell death, which all contribute to fibrosis. As a consequence of the overall slower liver disease progression and increased viral clearance in women, the disease burden from HCV infection is found predominantly in men. Although some studies have suggested higher sustained virologic response rates in HCV-infected women receiving dual therapy for HCV infection, this seems to be less important in the direct-acting antiviral era, when response rates for HCV therapy have increased so substantially that baseline demographic factors seem to have less of an effect on overall rates of cure.